Comparative study on extraction of virgin coconut oil with the aid of partially purified protease from seabass pyloric caeca and commercial trypsin. Issue 11 (27th August 2019) - Patil, Umesh; Benjakul, Soottawat
Abstract: Coconut milk was hydrolyzed by partially purified protease from seabass pyloric caeca (PPSP) and commercial trypsin (CT) at various levels (5 and 10 unit/g protein) at 60°C for different hydrolysis times (0–150 min). At the same protease level and hydrolysis time, higher degrees of hydrolysis and larger droplet size were found in coconut milk hydrolyzed by PPSP, compared to CT. The highest virgin coconut oil (VCO) yield (77.34%) was observed after the sample was hydrolyzed for 150 min by PPSP (10 units/g protein). Protein patterns indicated that coconut milk proteins were more prone to hydrolysis by PPSP, compared to CT. A marked difference was not found in physicochemical properties of commercial VCO and VCO separated from coconut milk using PPSP. Therefore, VCO could be extracted using PPSP under optimal condition, wherein the extraction could be accomplished within a short time with high yield. Practical applications: In virgin coconut oil (VCO) manufacture, the yield of VCO and cost of the commercial enzyme are of main concern. Therefore, cheap source of proteases, particularly proteases from seabass pyloric caeca, can be a promising alternative for the manufacture of VCO. Therefore, the cost associated with commercial enzymes could be reduced and the proteases from seabass processing byproducts were better exploited.